Influence of app usability and learning environment on student behavior in mobile-based marketing education in Malaysian higher learning institutions / Rozita Naina Mohamed ... [et al.] - Mohamed, Rozita Naina; Borhan, Halimahton; Rusli, Mohd Saifullah; Abd Hafiz, Khalilah; Othman, Azhana; Ridzuan, Abdul Rahim; Md Razak, Mohamad Idham; Marmaya, Najihah Hanisah (Faculty of Business and Management ; UiTM Press, 2024)
The increasing integration of mobile-based platforms in higher education, particularly within marketing education, has transformed learning dynamics by enabling students to engage through accessible digital tools. However, while internet and smartphone usage continue to grow in Malaysia, student engagement levels with mobile learning apps remain inconsistent. This study investigates how app usability (ease of use) and the learning environment influence student engagement behaviors within mobile-based marketing education in Malaysian higher education institutions. Using a quantitative approach, data were collected through a survey of 115 marketing students from public and private universities in Malaysia who have experience learning through mobile apps. The analysis, conducted using SPSS, indicates that both app usability and a supportive learning environment significantly contribute to positive student engagement behaviors, such as increased participation. The findings highlight that an intuitive, easy-to-use mobile platform within an encouraging educational environment fosters higher engagement in digital learning settings. This research provides valuable insights for educators and developers of mobile learning tools, underlining the need to prioritize usability and environmental support to optimize student engagement. The study’s implications can inform strategies for enhancing student interactions with digital marketing content, offering practical guidance for stakeholders aiming to elevate mobilebased educational experiences in Malaysia’s higher education sector.